ChemInform Abstract: Radical—Radical Cross‐Coupling for C—S Bond Formation. Issue 39 (September 2016) - Huang, Zhiliang; Zhang, Dongchao; Qi, Xiaotian; Yan, Zhiyuan; Wang, Mengfan; Yan, Haiming; Lei, Aiwen
Abstract: The preliminary mechanism of this reaction is revealed by radical‐trapping experiments, DFT calculations and kinetics, indicating that the C—S bond is formed through cross‐coupling of a thiyl radical and an aryl radical cation.